ANALYSIS OF THE KAZAKH CYBER TOURNAMENTS PLATFORM“PINGER.KZ” - Karazhan, Bekassyl; Alimanova, Madina; Alseitova, Akerke (Journal of Emerging Technologies and Computing, 2023)
Worldwide experts presume further growth of videogames field and suggest solutions according to the actual statistics. Despite the remarkablesuccesses of the e-athletes from Kazakhstan in a worldwide arena, there is a lack of statistical data on the local cybersport. Therefore, the research was conducted to provide prospective researchers in fields like gamification, eSport and media with actual data. The given scientific paper uses the data collected and analysed from the largest cyber tournament platform in Kazakhstan “Pinger.kz”. The analysed information is about tournaments that took place since the website launched in 2019 to 2021. The libraries of Python for data analysis as BeautifulSoup, requests, matplotlib and Apache tools were used. The aim of the work is to collect and make data analysis for future research. The paper identifies the most popular games among kazakh players in order to use this data in the research on gamification. Parsed data results show the development of the local cybersport and confirm worldwide trends.